Intelectualul român în tranziţie. Poziţionări după 1989 - Ivancu, Ovidiu (Studia Romanica Posnaniensia, 2014)
The present paper aims at analysing the trajectories of the Romanian intellectuals immediately after the Revolution in 1989, and the fall of Communism. During the Communist years, the term itself (intellectual) had been used with ideological connotations. The intellectual (as a social value) was discussed according to the Marxist ideology, taking into consideration his concrete usefulness and his contribution to the Communist society. Immediately after 1989, the fundamental dilemma faced by the Romanian intellectual represents the necessity of the implication of the intellectuals inside the society or, on the contrary, the isolation in an Ivory Tower of creation. The second challenge aimed at the necessity of synchronizing the Romanian elite with the European one; the topics for debate in Western and Eastern Europe during the Cold War were fundamentally different. The purpose of this paper is to analyse the influence and the commitment of the Romanian intellectuals in reshaping the Post-Communist Romanian society.